Systematic investigation of the effects of an anionic surface active ionic liquid on the interfacial tension of a water/crude oil system and its application to enhance crude oil recovery. Issue 11 (2nd November 2019) - Liu, Jingping; Huang, Pan; Feng, Qing; Lian, Peng; Liang, Yipu; Huang, Wenjian; Yan, Hui; Jia, Han
Abstract: A typical anionic surface active ionic liquid (SAIL), 1-butyl-3-methyl-imidazolium dioctylsulfosuccinate (BMOT), was introduced to chemical enhanced oil recovery. The ability of BMOT to reduce the interfacial tension (IFT) of water/crude oil was evaluated for its potential application in surfactant flooding. Compared with the traditional anionic surfactant AOT and another anionic SAIL 1-butyl-3-methylimidazolium dodecyl sulfate used in the control experiments, the effects of intramolecular electrostatic attraction and size match were employed to interpret the high interfacial activity of BMOT. The effects of salt and temperature on the water/crude oil IFT further verified the proposed mechanisms. Moreover, BMOT exhibited a satisfactory displacement performance to greatly improve the crude oil recovery (12.5% of the initial oil in place) in core flooding tests. Graphical Abstract: UF0001